2008
DOI: 10.1080/10242420802332558
|View full text |Cite
|
Sign up to set email alerts
|

Cutinase and pectinase in cotton bioscouring: an innovative and fast bioscouring process

Abstract: This manuscript describes the potential of a cutinase from the fungus Fusarium solani pisi for cotton wax degradation in order to design an efficient low temperature scouring process. The main characteristics, relevant to cotton wax removal with F. solani pisi cutinase are given. The additive effect of cutinase on pectinase was investigated and optimum incubation conditions were determined. Compatibility of cutinase with surfactants, essential for the rapid migration of enzymes into the fabric, is explored. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 24 publications
3
23
0
Order By: Relevance
“…Earlier reports showed that the fungal cutinase from Fusarium solani pisi has potential use for cotton cuticle degradation and exhibits a good synergistic effect with pectinase, an enzyme utilized to degrade pectin, in the scouring of cotton fiber (1,7,8,14). Moreover, site-directed mutagenesis has been performed to replace the specific amino acid residues near the active site of cutinase (3) to improve its hydrolytic activity toward polyesters.…”
mentioning
confidence: 99%
“…Earlier reports showed that the fungal cutinase from Fusarium solani pisi has potential use for cotton cuticle degradation and exhibits a good synergistic effect with pectinase, an enzyme utilized to degrade pectin, in the scouring of cotton fiber (1,7,8,14). Moreover, site-directed mutagenesis has been performed to replace the specific amino acid residues near the active site of cutinase (3) to improve its hydrolytic activity toward polyesters.…”
mentioning
confidence: 99%
“…Over the years, biotechnology has been employed in the textile fi bre processing such as fl ax and kenaf retting , ramie fi bre extraction (Zheng et al 2001;Basu et al 2011;Basu et al 2009), cotton bio-scouring (Agrawal et al 2008;Rajendran et al 2011), silk degumming (Arami et al 2007), wool functionalization (Queiroga et al 2007;Hossain et al 2009), etc.…”
Section: Biotechnological Fi Bre Extraction In Bamboomentioning
confidence: 98%
“…The necessary information and knowledge about the low-temperature wax removal, pectin removal, efficient wetting and use of chelators is available now (Agrawal et al 2007(Agrawal et al , 2008. The optimum conditions for enzymatic scouring are 50 mM Tris -HCl buffer, pH 8 -9, at 30 ° C, 1 g Triton X-100 L -1 , 2 g Baysolex L -1 as chelator and enzyme concentration of 100 U g-fabric -1 and 52 U g-fabric -1 for cutinase and pectinase, respectively.…”
Section: Ultrasound-assisted Benign One-step Cotton Scouringmentioning
confidence: 99%
“…The diffusion-based slow scouring process can be converted to a faster process by effi cient wetting and by intensifying mass transport. Effi cient wetting in cotton scouring is possible with non-ionic surfactants (Lenting et al 2002;Agrawal et al 2008). To intensify the mass transport in a textile processes, techniques such as the use of vacuum technology (Lenting & Warmoeskerken 2004) and ultrasound are being investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation